Penyebab Krisis Finansial Global tahun 2008: Kegagalan Financial Development dalam Mendorong Pertumbuhan dan Stabilitas Ekonomi - Yohanes William Santoso (Jurnal Hubungan Internasional, 2018)
The Global Financial Crisis has raised questions for economists on the causes of the issue and how to prevent similar case in the future. One of the causes of the crisis was a large and rapid increase of credit accumulation in the United States (US) on the period of 2000 to 2007. While according to the theory of Financial Development, credit is one of the indicator that shows the ongoing national financial system. Credit includes the access get credit and the ability of financial institution to lend credit. Both can be seen in the United States, proved by the ease of access to home loans and increasing amount of subprime mortgages. In accordance with the theory of financial development, the US economy should had experienced growth and stability. However, the rapid increase of credit accumulation in US has led to instability and crisis. The anomaly proves the failure of Financial Development and encourage the International Monetary Fund (IMF) to review the theory and prove its relevance in explaining economic growth and stability.